COVERAGE AND CAUSES OF MISSED HAEMOPHILUS INFLUENZAE TYPE B VACCINATION IN URBAN AND RURAL AREAS OF PESHAWAR - Naeem, Mohammad; Adil, Muhammad; Abbas, Syed Hussain; Khan, Muhammad Zia Ul Islam; Naz, Syeda Maria; Khan, Ayasha; Khan, Muhammad Usman (Journal of Ayub Medical College Abbottabad, 2011)
Background: Haemophilus influenza type b (Hib) is a major cause of morbidity and mortality in Pakistan. Hib vaccine was introduced in 2009 in EPI programme. The purpose of this study was to find out the coverage and factors associated with non-immunization of Hib in urban and rural areas of Peshawar. Methods: Data was collected through random sampling in Peshawar University, Peshawar Saddar, Hashtnagri, Naway Kalay and Pawaka from 9th to 19th of June 2010. A questionnaire was used to interview parents of 600 children aged 1 year and below about demographics, Hib vaccination status, reasons for missed vaccination and views on immunization. Pearson's Chi-square test was used for statistical testing, and p<0.05 was considered significant. Results: Completely vaccinated children were 64.2%, 25% not vaccinated at all, and 11% were incompletely vaccinated. The reasons for not vaccinating were lack of awareness (26%), family problem/mother busy (18%), centre too far (16.9%), wrong ideas (12.2%), fear of reaction (5.4%), child illness (8.1%) and miscellaneous causes (13.7%). Conclusion: Low Hib vaccination coverage in Peshawar is mainly due to low awareness among people, poor economic conditions and illiteracy. Keywords: Hib, Vaccination, Immunization, EPI, Haemophilus influenzae, Influenza